1995
DOI: 10.1042/bj3101021
|View full text |Cite
|
Sign up to set email alerts
|

The role of palmitoylation of the guanine nucleotide binding protein G11α in defining interaction with the plasma membrane

Abstract: Mutations of Cys-9 to serine, Cys-10 to serine and a combination of both alterations were produced in a cDNA encoding murine G11 alpha to potentially interfere with the ability of the expressed polypeptides to act as substrates for post-translational palmitoylation. Each of these mutants and the wild-type protein were expressed in simian COS-1 cells. Mutation of either cysteine-9 or cysteine-10 decreased the degree of palmitoylation of the protein by some 80% compared with the wild-type, while the double mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…2). Both of these mutants have been shown to partition between membrane and cytosol much less effectively than wild type G␣ 11 (20,21), and this thus restricts their relative membrane concentration compared with the receptor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). Both of these mutants have been shown to partition between membrane and cytosol much less effectively than wild type G␣ 11 (20,21), and this thus restricts their relative membrane concentration compared with the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that G␣ 11 can be post-translationally acylated on both Cys 9 and Cys 10 (20) and that mutation of both of these amino acids to Ser prevents membrane association of the G protein (20,21). Co-transfection of EF88 cells with the ␣ 1b -adrenoreceptor and C9S,C10S G␣ 11 thus also failed to result in a phenylephrine-mediated elevation of [Ca 2ϩ ] i (Fig.…”
Section: And D)mentioning
confidence: 99%
See 2 more Smart Citations
“…3B . These sites include Cys 9 and Cys 10 within the ␣ -subunit of the heterotrimeric G-protein, G 11 ( 32 ), Cys 181 and Cys 184 of H-Ras ( Fig. 2A, B, and see reference [ 27 ]), as well as 6 Cys residues within SNAP23, of which 4 are conserved in its betterstudied homolog SNAP25, a known S -palmitoylated protein ( 33 ).…”
Section: Mass Spectrometry-coupled Acyl-rac For Identifi Cation Of S mentioning
confidence: 99%